Ответ:
3
Пошаговое объяснение:
(9 7/12 - 8 11/12) : 2/9 = 9 7/12 - 8 11/12 = 8/12 : 2/9 = 8/12 * 9/2 = 4/4(то есть 1) * 3/1(то есть 3) = 1*3 = 3
[tex]9\frac{7}{12} -8\frac{11}{12} =8 \frac{19}{12} -8\frac{11}{12}= \frac{8}{12} } \\\\\\\frac{8}{12} : \frac{2}{9} = \frac{8}{12} * \frac{9}{2} =3[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
3
Пошаговое объяснение:
(9 7/12 - 8 11/12) : 2/9 = 9 7/12 - 8 11/12 = 8/12 : 2/9 = 8/12 * 9/2 = 4/4(то есть 1) * 3/1(то есть 3) = 1*3 = 3
[tex]9\frac{7}{12} -8\frac{11}{12} =8 \frac{19}{12} -8\frac{11}{12}= \frac{8}{12} } \\\\\\\frac{8}{12} : \frac{2}{9} = \frac{8}{12} * \frac{9}{2} =3[/tex]